PEMBERDAYAAN KELOMPOK TANI CATURHARJO MELALUI TRANSFER TEKNOLOGI SMART FARMING GREENHOUSE SEBAGAI PERCONTOHAN BUDIDAYA MELON - Mukasi Wahyu Kurniawati; Desi Kiswiranti; Raden Fatchul Hilal (Jurnal Abdi Insani, 2026)
The Ngudi Mulyo Farmers Group in Caturharjo, Sleman, faces challenges in horticultural cultivation due to conventional methods. The main problems are the wasteful water consumption of manual irrigation (20-25 L/plant) and the high risk of crop failure (30-70%) due to fungal attacks triggered by uncontrolled humidity. Farmers need to be introduced to more efficient and protected technologies. This community service (PkM) activity aims to empower partners by transferring smart farming greenhouse technology packages as a pilot project. The main objective is to provide farmers with experience growing crops using efficient, pest-free technology that produces maximum yields in a controlled environment. The method used is Participatory Action Research (PAR), involving 20 active farmers in five stages: (1) Socialization and FGD, (2) Technical training, (3) Implementation and installation of technology, (4) Intensive mentoring, and (5) Program evaluation. The core activity is the installation of a 5x10 meter pilot greenhouse with 99 melon plants, equipped with an innovative drip irrigation system integrated with solar panels. Results: This program successfully implemented one pilot smart farming greenhouse unit that is 100% operational. The innovative solar-powered drip irrigation and automatic fertilization system has proven to be successful and functioning well. Partners have completed one melon planting cycle (3 months) under intensive mentoring, thus gaining direct experience in operating precision cultivation technology that is water efficient and pest-free. This pilot program has successfully transferred integrated smart farming technology. Partner farmers now have experience and a technology prototype for efficient and protected cultivation, which is expected to be replicated on a larger scale based on the pilot harvest results.